Prognostic value of total testosterone levels in patients with acute coronary syndromes. (1st June 2019) - Gencer, Baris; Vuilleumier, Nicolas; Nanchen, David; Collet, Tinh-Hai; Klingenberg, Roland; Räber, Lorenz; Auer, Reto; Carballo, David; Carballo, Sebastian; Aghlmandi, Soheila; Heg, Dik; Windecker, Stephan; et al.
Abstract: Background: Endogenous testosterone levels decrease in men with aging. Controversies persist regarding the screening and treatment of low testosterone levels in patients with acute coronary syndromes (ACS). Methods and results: Total serum testosterone levels were measured in 1054 men hospitalized for ACS that were part of a Swiss prospective cohort. Total testosterone levels were classified first in tertiles and using the cut-off of 300 ng/dL. Primary endpoint was all-cause mortality at one year. Cox regression models adjusting for the GRACE score (composite of age, heart rate systolic blood pressure, creatinine, cardiac arrest at admission, ST segment deviation, abnormal troponin enzyme and Killip classification), preexisting diabetes and inflammation (high-sensitivity C-reactive protein). A total of 430 men (40.8%) had total testosterone levels ≤300 ng/dL. Low total testosterone levels were correlated with lower high-density lipoprotein cholesterol and higher triglycerides, high-sensitivity C-reactive protein, high-sensitivity troponin T, N-terminal-pro B-type natriuretic peptide and glucose levels (all p  < 0.01). Patients in the lowest testosterone tertile had a mortality rate at one-year of 5.4% compared with 2.9% in the highest tertile with an unadjusted hazard ratio of 1.92 (95% confidence interval 0.96–1.90, p  = 0.095) and adjusted hazard ratio of 1.26 (95% confidence interval 0.57–2.78, p  = 0.565). In an exploratory analysis, the highest mortality rate (10.3%) was observed in men aged >65 years old belonging to the lowest testosterone tertile. Conclusion: In this large population of men with ACS, we found a prevalence of low total endogenous testosterone levels of almost 40%. However, low testosterone levels were not significantly associated with mortality after adjustment for high-risk confounders.